2010
DOI: 10.1002/cae.20506
|View full text |Cite
|
Sign up to set email alerts
|

Developing the TriLab, a triple access mode (hands‐on, virtual, remote) laboratory, of a process control rig using LabVIEW and Joomla

Abstract: Laboratory education is a core part of engineering curricula; engineering students generally prefer to work on something real. The classical mode and the oldest form of laboratory education is the hands-on mode. Advances in information and communication technologies have contributed to the laboratory education by creating two new modes, the simulated (virtual) mode and the online controlled mode (remote). Recently, developments or utilizations of hybrid structures of two types (e.g., virtual and hands-on, or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 29 publications
(34 reference statements)
0
32
0
7
Order By: Relevance
“…This novel laboratory model combines the three access modes (Hands-On, Virtual, and Remote) in one unifying software package (the TriLab), by using LabVIEW (Abdulwahed & Nagy, 2013). The focus of our interest is in the virtual mode, which is the Process Control Virtual Laboratory (PCVL).…”
Section: Engineering -Non Roboticmentioning
confidence: 99%
“…This novel laboratory model combines the three access modes (Hands-On, Virtual, and Remote) in one unifying software package (the TriLab), by using LabVIEW (Abdulwahed & Nagy, 2013). The focus of our interest is in the virtual mode, which is the Process Control Virtual Laboratory (PCVL).…”
Section: Engineering -Non Roboticmentioning
confidence: 99%
“…The concept of the Trilab [6,86,91], blended pedagogically with Kolb's Experiential Learning theory [80] were utilized in realizing the closed-loop model, together with other elements. The Trilab concept indicates the utilization of three laboratory access modes for enriching experiential learning, via virtual, hands-on, and remote experiments..…”
Section: The Fpga Laboratory Course Design Methodologymentioning
confidence: 99%
“…The results showed that the students who used the blended approach scored significantly higher on conceptual understanding and complex problem solving. Another study (Abdulwahed & Nagy, 2013) in engineering domain, used the blended approach, involving hands-on and virtual lab, and remote lab additionally. The three modes contributed to the maximization of learning outcomes as well as students' motivation.…”
Section: Blended Usage Approachmentioning
confidence: 99%